Health Care Providers and Human Trafficking: What do They Know, What do They Need to Know? Findings from the Middle East, the Caribbean, and Central America - Viergever, Roderik F.; West, Haley; Borland, Rosilyne; Zimmerman, Cathy (Frontiers in Public Health, 2015)
Background: Human trafficking is a crime that commonly results in acute and chronic physical and psychological harm. To foster more informed health sector responses to human trafficking, training sessions for health care providers were developed and pilot-tested in the Middle East, Central America, and the Caribbean. This study presents the results of an investigation into what health care providers knew and needed to know about human trafficking as part of that training program. Methods: Participants attended one of seven two-day training courses in Antigua and Barbuda, Belize, Costa Rica, Egypt, El Salvador, Guyana, and Jordan. We assessed participants’ knowledge about human trafficking and opinions about appropriate responses in trafficking cases via questionnaires pre-training, and considered participant feedback about the training post-training. Results: 178 participants attended the trainings. Pre-training questionnaires were completed by 165 participants (93%) and post-training questionnaires by 156 participants (88%). Pre-training knowledge about health and human trafficking appeared generally high for topics such as the international nature of trafficking and the likelihood of poor mental health outcomes among survivors. However, many participants had misconceptions about the characteristics of trafficked persons and a provider’s role in responding to cases of trafficking. The most valued training components included the “Role of the Health Provider,” “Basic Definitions and Concepts,” and “Health Consequences of Trafficking.” Discussion: Training health care providers on caring for trafficked persons has the potential to improve practitioners’ knowledge about human trafficking and its health consequences, and to increase safe practices when responding in cases of trafficking. This study provides lessons for the design of training programs on human trafficking that aim to help health care providers identify and refer victims, and provide care for survivors.